2014
DOI: 10.5539/res.v6n2p17
|View full text |Cite
|
Sign up to set email alerts
|

Student-athletes’ Evaluation of Coaches’ Coaching Competencies and Their Sport Achievement Motivation

Abstract: The primary concerns of this study is whether universities' sport coaches possess good coaching competency skills in bringing up potential athletes for the country. What are coaches' coaching competency levels? Do their competencies capability able to contribute significantly to sport achievement motivation of student-athletes? Thus, this study was designed to evaluate the competency level of coaches and student-athletes' achievement motivation at the Higher Educational Institutions (HEI) in sports competition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…The analysis of coaches’ competencies in team sports in four areas (motivation, game strategy, technique and character-building competencies) showed that improving coaches’ psychological and tactical skills and their ability to recognize skills, together with a positive attitude towards sport, can help to improve athletes’ confidence in the work of coaches ( 77 ). Lim et al ( 78 ) found that the competence levels of coaches did not differ significantly by gender and performance of student athletes, but did differ significantly by sport type, between team and individual sports. The competency model proved to be a useful tool for sports organizations to identify and recruit coaches and for coaches to apply coaching planning strategies to ensure the effectiveness of their work.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of coaches’ competencies in team sports in four areas (motivation, game strategy, technique and character-building competencies) showed that improving coaches’ psychological and tactical skills and their ability to recognize skills, together with a positive attitude towards sport, can help to improve athletes’ confidence in the work of coaches ( 77 ). Lim et al ( 78 ) found that the competence levels of coaches did not differ significantly by gender and performance of student athletes, but did differ significantly by sport type, between team and individual sports. The competency model proved to be a useful tool for sports organizations to identify and recruit coaches and for coaches to apply coaching planning strategies to ensure the effectiveness of their work.…”
Section: Discussionmentioning
confidence: 99%
“…(Chiu, Mahat, Ahmad Marzuki, & Poy Hua, 2014) Stated that coaches who had competence show differences in their use and training style in providing motivation, explaining strategies and playing techniques, and building the athlete's character. That was because that difference would have a different impact on the training process results (Chiu et al, 2014) stated that coach's competency showed differences in the use and style of training in providing motivation and explaining playing strategies and techniques and when building athlete character. That was because that difference would have a different impact on the results of the training process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the competence for any position in the sports-related vocational field, including that of the sports coach, consists of a combination of knowledge, skills, and certain psychosocial senses [21,22,[25][26][27][28]. However, sports coach competency and its components could differ from one community to another since this competency may reflect the cultural, historical, societal, economic, and political contexts of the community [29][30][31][32][33]. Similarly, the relative importance of each required competence and its components could differ according to this context.…”
Section: Sports Coach Competencementioning
confidence: 99%